Analysis of the effect of electric component on the indicators of the quality of traction system of electrical supply (Transport systems and technologies, 2019)
The article describes and substantiates characteristics of electric power quality parameters that influence the work of traction and auxiliary drives of electric railroad rolling stock. It is analyzed how traction and auxiliary drives of an electromotive force influence on each of the parameters of electric power of the traction power supply system. It is shown how the work of electric drives affects the random nature of processes occurring in the traction power system of railways. The methodology of calculation of the allowable contribution of consumers for the indicators of electricity quality, as well as the actual contribution of distortions of consumers in the system of traction power supply is given. For such indicators of electric power quality as deviation of voltage and frequency and distortion of the nonsinusoidality of the voltage curve for electric lines of the VL-80 series, allowable consumer inputs and actual consumption inputs are calculated, taking into account the distortion of these indicators by other consumers of electric power. Calculations were made taking into account the random nature of the electromagnetic processes occurring in the traction power system, and provided that the probability of output of the quality index with allowable limits is 0.95. Measures to reduce the impact of these drives on the power quality parameters of the traction power supply system are proposed.a
Keywords: indicators of electric power quality, traction system of power supply, traction drive, auxiliary drive